HARGA DALAM PERSPEKTIF ISLAM (Mazahib, 2007)
In every business, pricing is a very important stage. This is because price will influence the status and performance of company finance; let alone the customers’ perception and positioning the brand. Failure in pricing will have long terms impacts on the company’s existence. In Islam, price becomes a standard of exchange between money and goods/services that a buyer and a seller must be willing. Any methods may be employed to price as long as they fulfill some requirements underlined by Islam.